The effect of a 12-week physiotherapy program on lower extremity function and gait in children with isolated gastrocnemius tightness - TUNCER D.; Eren Zengin F.; ŞENARAN H.; UZER G. (My University, 2025)
Background: Isolated gastrocnemius tightness (IGT) limits ankle dorsiflexion with the knee extended. This study evaluated a 12-week physiotherapy program’s effects on lower extremity function and gait in children with IGT. Materials and methods: A single-group pre-post interventional design was used, including 30 children aged 6–12 years with bilateral IGT. Active and passive ankle dorsiflexion and lower extremity flexibility were measured. IGT was accepted based on passive dorsiflexion as < 10° with the knee extended and an increase of ≥ 10° with the knee flexed, according to the Silfverskiold test. The physiotherapy program involved stretching, strengthening, and functional exercises targeting the foot and ankle. Outcomes were assessed using the Navicular Drop Test (NDT), Foot Posture Index-6 (FPI-6), the Lower Extremity Functional Scale (LEFS), the Sit-to-Stand Test (SST). Gait was recorded on video, analyzed using Kinovea® software, and deviations were scored using the Edinburgh Visual Gait Score (EVGS). Results: Bilateral improvements were observed in dorsiflexion with knee extension (ηp2 = 0.888–0.956), dorsiflexion with knee flexion (ηp2 = 0.445–0.749), inversion (ηp2 = 0.300–0.362), and eversion (ηp2 = 0.202–0.280). Foot posture improved on both sides in NDT (ηp2 = 0.363) and FPI-6 (ηp2 = 0.357–0.642). Functional outcomes showed significant changes in SST (ηp2 = 0.336), LEFS (ηp2 = 0.649), and EVGS (ηp2 = 0.548). Conclusion: This study highlights the clinical value of physiotherapy in improving foot posture, lower extremity function, and gait in children with IGT. The findings support including targeted physiotherapy to address musculoskeletal impairments from gastrocnemius tightness. ClinicalTrials.gov ID: NCT06678139, registration date: April 11, 2024.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Rehabilitasyon; Clinical Medicine (Med); Clinical Medicine; Rehabilitation; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Children; exercise therapy; foot posture; gait; gastrocnemius; muscle tightness